2004
DOI: 10.1074/jbc.m406631200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Intercellular Adhesion Strength in Fibroblasts

Abstract: The regulation of adherens junction formation in cells of mesenchymal lineage is of critical importance in tumorigenesis but is poorly characterized. As actin filaments are crucial components of adherens junction assembly, we studied the role of gelsolin, a calciumdependent, actin severing protein, in the formation of N-cadherin-mediated intercellular adhesions. With a homotypic, donor-acceptor cell model and plates or beads coated with recombinant N-cadherin-Fc chimeric protein, we found that gelsolin spatial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 64 publications
1
34
0
Order By: Relevance
“…The molecular composition of these junctions is simple. Apparently, the coexistence of N-cadherin and cadherin-11 is typical for puncta adhaerentia of diverse mesenchymal cells and tissues (e.g., Okazaki et al 1994;Hoffmann and Balling 1995;Kimura et al 1995;Simonneau and Thiery 1998;Hinz et al 2004), as are cytoplasmic plaques comprising α-and β-catenin, together with protein p120 and afadin, whereas appreciable amounts of other plaque proteins seem to be lacking (for references, see Straub et al 2003;Godsel et al 2004;Irie et al 2004; for a possible role of gelsolin in the anchorage of the actin filaments at adhering junctions of fibroblasts and probably also other mesenchymally derived cells, see Chan et al 2004). The functional importance of the molecular complement of these puncta adhaerentia in the differentiation of mesenchymal cells and tissue formation is indicated by the developmental defects described for mice lacking N-cadherin or cadherin-11 or both (Radice et al 1997;Horikawa et al 1999;Luo et al 2004;Kostetskii et al 2005) and by the general importance of cadherin-11 in the regulation of cell motility and cell-cell interaction in the dynamics of mesenchymal cells (cf.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular composition of these junctions is simple. Apparently, the coexistence of N-cadherin and cadherin-11 is typical for puncta adhaerentia of diverse mesenchymal cells and tissues (e.g., Okazaki et al 1994;Hoffmann and Balling 1995;Kimura et al 1995;Simonneau and Thiery 1998;Hinz et al 2004), as are cytoplasmic plaques comprising α-and β-catenin, together with protein p120 and afadin, whereas appreciable amounts of other plaque proteins seem to be lacking (for references, see Straub et al 2003;Godsel et al 2004;Irie et al 2004; for a possible role of gelsolin in the anchorage of the actin filaments at adhering junctions of fibroblasts and probably also other mesenchymally derived cells, see Chan et al 2004). The functional importance of the molecular complement of these puncta adhaerentia in the differentiation of mesenchymal cells and tissue formation is indicated by the developmental defects described for mice lacking N-cadherin or cadherin-11 or both (Radice et al 1997;Horikawa et al 1999;Luo et al 2004;Kostetskii et al 2005) and by the general importance of cadherin-11 in the regulation of cell motility and cell-cell interaction in the dynamics of mesenchymal cells (cf.…”
Section: Discussionmentioning
confidence: 99%
“…This focusing of the Ca 2+ entry to the adhesion sites can explain how a new Ca 2+ wave is triggered at the cell-cell junction site upon stress fibre contraction in our experiments. Moreover, using cadherin-coated beads and micromanipulated partner cells, McCulloch and co-workers have demonstrated that force applied via cadherin contacts triggers a Ca 2+ response in fibroblastic cells, leading to local actin reorganisation (Chan et al, 2004;Ko et al, 2001a;Ko et al, 2001b). The authors proposed a model of cadherin-mediated mechanotransduction where actin-mediated reinforcement of adherens junctions represents a mechanoprotective response to high forces (Janmey and McCulloch, 2007;Ko and McCulloch, 2001).…”
Section: +mentioning
confidence: 99%
“…The contractile actin cytoskeleton has been shown to increase intercellular adhesion by supporting lateral clustering of cadherins (Bershadsky, 2004;Chan et al, 2004;Chu et al, 2004;Delanoe-Ayari et al, 2004;El Sayegh et al, 2007;Gumbiner, 2000;Mege et al, 2006). To block this action, we put into contact differentiated myofibroblasts in the presence of cytochalasin D, which disassembled stress fibers of myofibroblasts on AFM cantilevers (Fig.…”
Section: Ob-cadherin Junctions Exhibit Three Distinct Force Statesmentioning
confidence: 99%